Dacarbazine alone or associated with melanoma‐bearing cancer pain model induces painful hypersensitivity by TRPA1 activation in mice. Issue 10 (8th October 2019) - Brusco, Indiara; Li Puma, Simone; Chiepe, Kelly Braga; da Silva Brum, Evelyne; de David Antoniazzi, Caren Tatiane; de Almeida, Amanda Spring; Camponogara, Camila; Silva, Cássia Regina; De Logu, Francesco; de Andrade, Vanessa Moraes; Ferreira, Juliano; Geppetti, Pierangelo; et al.
Abstract : Antineoplastic therapy has been associated with pain syndrome development characterized by acute and chronic pain. The chemotherapeutic agent dacarbazine, used mainly to treat metastatic melanoma, is reported to cause painful symptoms, compromising patient quality of life. Evidence has proposed that transient receptor potential ankyrin 1 (TRPA1) plays a critical role in chemotherapy‐induced pain syndrome. Here, we investigated whether dacarbazine causes painful hypersensitivity in naive or melanoma‐bearing mice and the involvement of TRPA1 in these models. Mouse dorsal root ganglion (DRG) neurons and human TRPA1‐transfected HEK293 (hTRPA1‐HEK293) cells were used to evaluate the TRPA1‐mediated calcium response evoked by dacarbazine. Mechanical and cold allodynia were evaluated after acute or repeated dacarbazine administration in naive mice or after inoculation of B16‐F10 melanoma cells in C57BL/6 mice. TRPA1 involvement was investigated by using pharmacological and genetic tools (selective antagonist or antisense oligonucleotide treatment and Trpa1 knockout mice). Dacarbazine directly activated TRPA1 in hTRPA1‐HEK293 cells and mouse DRG neurons and appears to sensitize TRPA1 indirectly by generating oxidative stress products. Moreover, dacarbazine caused mechanical and cold allodynia in naive but not Trpa1 knockout mice. Also, dacarbazine‐induced nociception was reduced by the pharmacological TRPA1 blockade (antagonism), antioxidants, and by ablation of TRPA1 expression. TRPA1 pharmacological blockade also reduced dacarbazine‐induced nociception in a tumor‐associated pain model. Thus, dacarbazine causes nociception by TRPA1 activation, indicating that this receptor may represent a pharmacological target for treating chemotherapy‐induced pain syndrome in cancer patients submitted to antineoplastic treatment with dacarbazine. Abstract : What's new? Acute and chronic pain syndromes, such as chemotherapy‐induced peripheral neuropathy, are extremely common among cancer patients, and can limit the use of chemotherapy. Several studies have indicated that the nerve receptor TRPA1 may be involved in this kind of pain. In this study, the authors used antisense, knockout, and pharmacological methods to conclude that the antineoplastic drug dacarbazine does induce pain signals via TRPA1 activation. This receptor may thus represent a valuable therapeutic target for treating chemotherapy‐induced pain.